Whole wheat bread enriched with silver fir (Abies alba Mill.) needles extract: technological and antioxidant properties. (20th December 2021) - Parenti, Ottavia; Albanese, Lorenzo; Guerrini, Lorenzo; Zanoni, Bruno; Zabini, Federica; Meneguzzo, Francesco
Abstract: BACKGROUND: The interest of consumers and market and scientific research for added‐value foods obtained with environmentally sustainable productive chains is increasing. Silver fir ( Abies alba Mill.) needles (SFNs), often by‐products of forest management and logging, represent an unexploited source of bioactive compounds. RESULTS: For the first time, SFN aqueous extract obtained through controlled hydrodynamic cavitation was used to enrich whole wheat flour bread. The first trial found that 35% SFNs extract addition was the absolute threshold of taste perception. The second trial investigated dough rheological properties and bread technological and antioxidant properties in samples enriched with 35% and 100% SFNs extract compared with the control (0% SFNs extract). SFNs extract significantly increased bread antioxidant capacity in both 35% and 100% SFN fresh breads by ~42.5% and ~87% respectively and in 100% SFNs bread samples after 72 h of storage by ~76%. Enrichment of 35% showed higher alveograph dough extensibility (~11%) and different bread texture in terms of hardness, springiness, and chewiness. Enrichment with 100% SFNs extract significantly improved dough and bread technological quality: it increased alveograph dough extensibility L (~18%), swelling index G (~8%), and flour strength W (~14%) and showed the highest increase in bread specific volume (~0.200 L kg −1 ). CONCLUSIONS: SFNs aqueous extract produced with controlled hydrodynamic cavitation appeared a valuable technical material for the manufacturing of added‐value and functional breads. © 2021 Society of Chemical Industry.